Technical and physical analysis of the 2014 FIFA World Cup Brazil: winners vs. losers - Rumpf, M. C.; Silva, J. R.; Hertzog, M.; Farooq, A.; Nassis, G. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The purpose of the present study was to investigate the technical and physical performance parameters that distinguish between teams winning and losing matches in the 2014 FIFA World Cup Brazil.